The past in them: celebrating BaTonga artefacts and visual cultural communication in Zimbabwe - Saidi, Umali (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2017)
Much has been written on BaTonga’s dislocation from the Zambezi Valley to pave way for the construction of the hydroelectric project and the aftermath effects on the BaTonga. BaTonga are characterised in these discourses as having lost their livelihoods and subsequently their culture. This article celebrates and advances that BaTonga took their culture with them especially as embodied in their cultural material objects such as the ncelwa. Using artefactual semiotics the article advances the argument that a view of BaTonga from a visual cultural communication perspective allows us to appreciate how BaTonga managed to carry with them key cultural values which have made them assume the cultural identity they have today.